Impact of Institutional Factors on the Technological Level in Metallurgy of Russian Federation - A. A. Blokhin; S. Ya. Dranev (Мир новой экономики)
The article determines the influence of institutional factors on the characteristics of the technological development of Russian metallurgy. We proposed several institutional criteria following identified three samples— Russian multinational corporations, large companies operating in many regions of Russia, the remaining companies operating at the local level. We investigated these samples in the context of several technological criteria. The main ones are access to modern technologies, level of production capacities, interaction with educational organizations. The study shows that the division of companies metallurgical companies into three institutionally different groups is accompanied by their stratification also by their technological level. The first group significantly surpasses the second and third by the volume of financing of technological innovations, the level of interaction with educational institutions, the level of interaction with research institutes and access to high technology. The differences between the second and third groups are also strongly pronounced. The approach described in the article makes possible the determination of the technological limitations in the metallurgical industry associated with its institutional features and shaping public policy, which takes into account the sensitivity of qualitatively different groups of businesses to stimulating measures.